"Structural Dissatisfaction": Academics on Safari in the Novels of Jennifer Egan. Issue 1 (19th October 2015) - Eve, Martin Paul
Jennifer Egan's acclaimed 2010 novel, A Visit from the Goon Squad, is a text populated by a disproportionately high number of, often unfulfilled, postgraduate researchers: "I'm in the PhD program at Berkeley", proclaims Mindy; "Joe, who hailed from Kenya […] was getting his PhD in robotics at Columbia"; "Bix, who's black, is spending his nights in the electrical-engineering lab where he's doing his PhD research"; while only Rebecca "was an academic star". Indeed, in this text, academia seems a place of misery, of "harried academic slaving", and, ultimately, of "immaturity and disastrous choices". Over the course of this article I will demonstrate that, in fact, Egan's critique of the university is an immanent meta-critique. While the history of the campus novel is often premised on hermetically sealing the campus (the genre usually functions through an explicit focus on a delineated campus space or, at least, predominantly upon the social milieu of the academy), Egan's novels seem to play on bursting the very notions of inside and outside that facilitate this genre, blurring the boundaries between fiction and critique; the leeching of the university into everyday life. She also, simultaneously, however, critiques the structures of labour upon which much of the academy is founded. While I will move towards Egan's latest novel, A Visit From the Goon Squad, throughout this article I will make reference to her entire novelistic canon, demonstrating that the treatment of academics throughout cannot be viewed as merely incidental, even if the appearances of such characters are sporadic and diffuse.